Epistemic Injustice in Brain Studies of (Trans)Gender Identity - Llaveria Caselles, Eric (Frontiers in Sociology, 2021)
This paper analyses the conceptualization of gender identity in neuroscientific studies comparing the brains of cisgender and transgender participants looking both at criteria of scientific adequacy and at the exclusion of relevant bodies of knowledge. The results of a content analysis show how the active ignoring of biosocial, developmental, mosaicist, contextualist and depathologizing approaches leads to internal conceptual inconsistencies, hermeneutical deficiencies and the upholding of questionable paradigms in the research field. Interviews with researchers involved in these brain studies reveal targeted and diffuse forms of testimonial injustice against alternative approaches, promoted by the hierarchical organizational arrangements of research teams in combination with careerist and economic logic of research. The analysis points to the exclusion of critical epistemologies of science and the historical oppression of trans people as epistemic agents as underlying hermeneutical deficiencies.